Mood Swing in The Gen Z Female Workforce : Understanding Emotional Dynamics et Work - Ni'matul Khoiriyah; Wahyu Eko Pujianto; Nafiah Ilhama Qurratuaini; Edita Rachma Kamila (Riwayat: Educational Journal of History and Humanities, 2025)
Generation Z faces various challenges in the world of work that ultimately affect the performance of individuals, especially generation Z women. This study aims to analyze the influence of mood swing and emotional dynamics on individual performance with individual religiosity acting as mediation. The sampling technique uses purposive sampling which is used for sample selection. This research was conducted in Java-Bali, involving 211 respondents targeting working Gen Z women. Data analysis was carried out using the quantitative method of SmartPLS 4.0 software. The results showed that mood swing and emotional dynamics had a significant effect on individual performance. In addition, individual religiosity strengthens the relationship between mood swing and individual performance, however, it does not have a significant effect, but individual religiosity weakens the relationship between emotional dynamics and individual performance but also has no significant effect. This research provides practical insights for Generation Z, especially women who work to understand how mood swings and emotional dynamics work in the workplace as well as individual religiosity responses to prosper self-peace in the world of work.